PENGARUH KERJASAMA TIM, BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN PONOROGO - Ersa Mayori Jayanti Fortuna; Heri Wijayanto; Sri Hartono (Gapenas Publisher, 2022)
The research was conducted to determine the effect of teamwork, workload and work dicipline on the performance of the Ponorogo Regency Population Control and Family Planning Office employees. The Object of this research is the Office of Population Control and Family Planning in Ponorogo Regency. The sample in this research were employees of the Department of Population Control and Family Planning, Ponorogo Regency, totaling 115 peoples using the Saturates Sampling technique. The method in this research is a quanitative research method. Methods of data collection using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that : (1) There is an influence between teamwork on the performance of the Population Control and Family Planning Office of Ponorogo Regency. (2) There is an influence between workload on the performance of the employees of the Population Control and Family Planning Office of Ponorogo Regency. (3) There is an influence between work discipline on the performance of the employees of the Office of Population Control and Family Planning in Ponorogo Regency. (4) There is an influence between teamwork, workload and work discipline on the performance of the Ponorogo Regency Population Control and Family Planning Service employees